Advanced Technology for Delivering Therapeutics 2017
DOI: 10.5772/65116
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Percutaneous Absorption on Skin by Plasma Drug Delivery Method

Abstract: Transdermal drug delivery (TDD) is a painless method of low-dose drug delivery. The advantages and disadvantages of transdermal drug delivery methods are named and basic methods such as using chemical enhancers, iontophoresis and electrophoresis are introduced. One of the promising methods make use of plasma which is generated in atmospheric pressure mostly in volume or on surface dielectric barrier discharge (DBD) or in plasma jet. As the plasma produces various particles according to the used gas, UV radiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 91 publications
(92 reference statements)
0
7
0
Order By: Relevance
“…Over the last two decades, many researchers paid attention to CAP to overcome the disadvantages of the conventional drug delivery systems and promote drug penetration. The skin properties can be changed temporarily to improve the drug transportation by CAP through various effects based on its multiple components (ions, heat, UV light, reactive oxygen species, and other reactive radicals) 16 . It has been proved that CAP could promote the percutaneous absorption of various substances and drugs including phenol red, GaHBr, 17 rhodamine B, 18 cyclosporine A, 19 and dextrans 20 in animal models and ex vivo permeation study, 21 whereas few clinical trials can be referred to.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, many researchers paid attention to CAP to overcome the disadvantages of the conventional drug delivery systems and promote drug penetration. The skin properties can be changed temporarily to improve the drug transportation by CAP through various effects based on its multiple components (ions, heat, UV light, reactive oxygen species, and other reactive radicals) 16 . It has been proved that CAP could promote the percutaneous absorption of various substances and drugs including phenol red, GaHBr, 17 rhodamine B, 18 cyclosporine A, 19 and dextrans 20 in animal models and ex vivo permeation study, 21 whereas few clinical trials can be referred to.…”
Section: Introductionmentioning
confidence: 99%
“…A higher level of skin resistance is associated with skin integrity and an intact barrier (Rachakonda et al, 2008), influencing methods such as iontophoresis (Roustit, Blaise & Cracowski, 2014). This method employs a non-invasive electric current at low voltages for the delivery of ionisable drugs into the skin (Shimizu & Krištof, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, the plasma-generated RONS are insufficient for treating various diseases [11]. Therefore, plasma medicine explores treatment not only via CAPs instead of drugs but also via combinations of CAPs and drugs, which can produce effects that cannot be produced by using a CAP or a drug alone [12]. For example, Guo et al found that CAPs could promote the effects of several classes of antibiotics, and hence acted as antibiotic sensitizers for the treatment of antibiotic-resistant bacteria that are involved in infectious diseases [13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Guo et al found that CAPs could promote the effects of several classes of antibiotics, and hence acted as antibiotic sensitizers for the treatment of antibiotic-resistant bacteria that are involved in infectious diseases [13]. Various reports predicted that the combination of CAPs and drugs may satisfy the requirements for the treatment of various diseases [12,14], and this combination is a promising approach in the field of plasma medicine; however, the mechanism is not well understood, which motivates us to conduct the present study.…”
Section: Introductionmentioning
confidence: 99%